Analisis determinan stunting pada baduta di Wilayah Kerja Puskesmas tahun 2016 - Basri Aramico; Zamratul Husna (Alma Ata University Press, 2016)
ABSTRACTBackgrounds: Stunting remains a problem that still needs to be considered by the government, because children with stunting decreased of intelligence (IQ) than children who are not stunting. Optimal growth can only be achieved by the intake of nutritious food and a healthy environment. In 2013, the prevalence of stunting in Aceh amounted to 37.2% consisted of 18% very short and 19.2% short. Based on the results of monitoring nutritional status report from Public Health Office in Pidie Jaya, the prevalence of stunting increased in the last two years. That percentage increased from 14.8% in 2014 and become 17% in 2015.Objectives: This study aims to determine of stunting of BADUTA in Puskesmas Ulim, Pidie Jaya district in the year of 2016.Methods: This research design is descriptive analytic by cross-sectional. The population in this study is all mothers who have BADUTA in Puskesmas Ulim in total of 75 respondents. The sampling method used is cluster sampling with total samples taken by 20% of the entire population from every six villagers from 30 villages. The primary data obtained directly by measuring the length of the child's body and through questionnaires by interview. The statistical test used is Chi-Square Test.Results: The study showed that 66.7% children experienced stunting, 70.7% children has less nutrition, 85.3% children does not received exclusive breastfeeding, 8.0% children with low birth weight babies, and 80.0% having infectious diseases. From the statistical analysis it can be concluded that there is a relationship between nutrient intake (p-value= 0.000), breastfeeding (p-value= 0.000), and infectious diseases (p-value= 0.029) with stunting. However, there is no relation between low birth weight (LBW) (p-value= 0.079) with stunting for BADUTA.Conclusions: There is significant correlation between nutrition, exclusive breastfeeding, infection disease with stunting of BADUTA meanwhile there is no significant correlation between LBW babies with stunting in Puskesmas Ulim at Pidie Jaya district.Keywords: stunting, nutrient intake, exclusive breastfeeding, LBW, and infectious diseases ABSTRAKLatar belakang: Stunting masih menjadi masalah yang harus diperhatikan pemerintah, dikarenakan anak penderita stunting mangalami penurunan intelligence quotient (IQ) dibandingkan dengan anak yang tidak stunting. Pertumbuhan yang optimal hanya dapat dicapai dengan asupan makanan yang bergizi serta lingkungan yang sehat. Tahun 2013 prevalensi stunting di Aceh sebesar 37,2 % terdiri dari 18,0% sangat pendek dan 19,2 % pendek. Berdasarkan hasil laporan pemantau status gizi Dinas Kesehatan Kabupaten Pidie Jaya prevalensi stunting mengakami peningkatan dakam dua tahun terakhir. Persentase peningkatan tersebut pada tahun 2014 sebesar 14,8%, meningkat menjadi 17% pada tahun 2015.Tujuan: Penelitian ini bertujuan untuk mengetahui analisis determinan stunting pada baduta di wilayah kerja Puskesmas Ulim Kabupaten Pidie Jaya Tahun 2016. Metode: Penelitian ini adalah penelitian deskriptif analitik dengan desain cross sectional. Populasi pada penelitian ini adalah seluruh ibu yang memiliki baduta di wilayah kerja Puskesmas Ulim sebanyak 75 responden, dengan metode sampling yang dipilih adalah cluster sampling, sampel yang akan diambil sebesar 20% dari seluruh populasi, dengan teknik gugus adalah dengan mengambil 6 desa dari 30 desa. Data primer diperoleh langsung melalui pengukuran panjang badan anak dan melalui kuesioner dengan cara wawancara. Uji statistik yang digunakan yaitu uji chi-square test.Hasil: penelitian menunjukkan bahwa sebanyak (66,7%) anak mengalami stunting, asupan gizi yang kurang (70,7%), yang tidak memberikan ASI eksklusif (85,3%), yang bayi berat lahir rendah (8,0%), dan yang ada penyakit infeksi (80,0%). Dari analisa statistik dapat disimpulkan bahwa ada hubungan antara asupan gizi (p=0,000), pemberian ASI (p=0,000), penyakit infeksi (p=0,029), dan tidak ada hubungan berat bayi lahir rendah (p=0,079) dengan stunting pada baduta. Kesimpulan: Ada hubungan yang bermakna antara asupan gizi, pemberian ASI Ekslusif, penyakit Infeksi dengan stunting pada baduta, dan tidak ada hubungan yang bermakna antara bayi berat lahir rendah dengan stunting pada baduta di Wilayah Kerja Puskesmas Ulim Kabupaten Pidie Jaya. KATA KUNCI: stunting, asupan gizi, ASI eksklusif, BBLR, penyakit infeksi